Impact of fluoroquinolones and aminoglycosides on P. aeruginosa virulence factor production and cytotoxicity. Issue 24 (22nd December 2022) - Foulkes, Daniel M.; McLean, Keri; Sloniecka, Marta; Rustidge, Sophie; Byrne, Dominic P.; Haneef, Atikah S.; Winstanley, Craig; Berry, Neil; Fernig, David G.; Kaye, Stephen B.
Abstract : The opportunistic pathogen Pseudomonas aeruginosa is one of leading causes of disability and mortality worldwide and the world health organisation has listed it with the highest priority for the need of new antimicrobial therapies. P. aeruginosa strains responsible for the poorest clinical outcomes express either ExoS or ExoU, which are injected into target host cells via the type III secretion system (T3SS). ExoS is a bifunctional cytotoxin that promotes intracellular survival of invasive P. aeruginosa by preventing targeting of the bacteria to acidified intracellular compartments. ExoU is a phospholipase which causes destruction of host cell plasma membranes, leading to acute tissue damage and bacterial dissemination. Fluoroquinolones are usually employed as a first line of therapy as they have been shown to be more active against P. aeruginosa in vitro than other antimicrobial classes . Their overuse over the past decade, however, has resulted in the emergence of antibiotic resistance. In certain clinical situations, aminoglycosides have been shown to be more effective then fluoroquinolones, despite their reduced potency towards P. aeruginosa in vitro . In this study, we evaluated the effects of fluoroquinolones (moxifloxacin and ciprofloxacin) and aminoglycosides (tobramycin and gentamycin) on T3SS expression and toxicity, in corneal epithelial cell infection models. We discovered that tobramycin disrupted T3SS expression and reduced both ExoS and ExoU mediated cytotoxicity, protecting infected HCE-t cells at concentrations below the minimal inhibitory concentration (MIC). The fluoroquinolones moxifloxacin and ciprofloxacin, however, up-regulated the T3SS and did not inhibit and may have increased the cytotoxic effects of ExoS and ExoU.